2011
DOI: 10.1007/bf03325245
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of working-memory deficits in patients with mild cognitive impairment and Alzheimer’s dementia using Wechsler’s Working Memory Index

Abstract: Workingmemory deficits are already present in MCI patients and worsen in AD patients, suggesting that working memory should be assessed as part of neuropsychological testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…Parra et al, 2011). In general, more consideration should be given to the assessment of the working memory domain in patients with early-stage Alzheimer's disease, notably amnestic MCI patients, as there is increasing evidence that working memory is already compromised in these patients (Belleville, Chertkow, & Gauthier, 2007;Belleville, Peretz, & Malenfant, 1996;Guild et al, 2014;Kessels, Molleman, & Oosterman, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Parra et al, 2011). In general, more consideration should be given to the assessment of the working memory domain in patients with early-stage Alzheimer's disease, notably amnestic MCI patients, as there is increasing evidence that working memory is already compromised in these patients (Belleville, Chertkow, & Gauthier, 2007;Belleville, Peretz, & Malenfant, 1996;Guild et al, 2014;Kessels, Molleman, & Oosterman, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although early and significant episodic memory impairment constitutes the clinical core diagnostic criterion of AD (Dubois et al, 2014), there is increasing evidence of early deficits in WM and executive function in patients with MCI and AD (Crawford et al, 2013;Gagnon and Belleville, 2011;Huntley and Howard, 2010;Kessels et al, 2011;Koppel et al, 2014). Moreover, fMRI studies have also suggested a possible subclinical impairment of WM capacity in healthy APOE ε4 carriers (Chen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported behavioral deficits in WM in individuals with MCI [9,10,11,12,13,14,15,16,17,18,19]. Specifically, these individuals have been found to have deficits in verbal [10,11,15,17,19], visual [9], spatial [13,14,18], and object-location WM memory [9,16]. Moreover, these WM deficits have been found in different MCI subtypes, including amnestic and nonamnestic MCI [12,19] and single- and multiple-domain MCI [12].…”
Section: Introductionmentioning
confidence: 99%